Social Housing Neighbourhoods in the 1950s in Génova and Madrid: The germ of a different kind of city - Guillem González-Blanch, María (Street Art & Urban Creativity, 2025)
In Italy and Spain, post-war industrialisation generated a large migration movement from the countryside to the city, which led to the massive construction of social housing in the 1950s. This paper deals with a comparative analysis of relevant cases of social housing neighbourhoods: the INA-CASA quartieri in Genoa and the INV's guided settlements in Madrid, highlighting the synergies between the housing policies adopted in the face of the housing crisis in both countries and the architectural and urban solutions that have an imported modernity in their genetics. The mix of uses and experimental typologies are innovative for the time, from the Caño Roto duplexes to Bernabó Brea's single-person dwellings. They constitute a fundamental episode in the history of 20th century architecture and creatively transform both cities, where public space takes on special relevance.